The Characteristics of Selective 3D Metal Additive Process Using Electrochemical Deposition and Nozzle Fluid Dynamics - Kim, Young-kuk; Kang, Donghwa; Kim, Hyung-rae; Kim, Sung-bin; Yoo, Bongyoung (Frontiers in Mechanical Engineering, 2020)
In this study, we investigated the characteristics of the three-dimensional (3D) additive printing process of pure copper(Cu) on metal substrates through the localized electroplating with precisely controlled nozzle fluid dynamics. In addition, we analyzed the characteristics of 3D shape formations in relation to the changes in the main electroplating factors, such as electrolyte temperature, applied current, nozzle pressure and distance between the working electrode and the nozzle. The variations of the surface texture and growth rate owing to these factors were confirmed and optimum condition was investigated. Finally, the successful fabrication of complicated 3D structures, such as micro coils and star-like pattern were demonstrated through the proposed method.